Development of Physics Textbooks Based on STEM Integrated to Quranic Verses in Traveling and Standing Waves Subject - Aulia Litsa Ariffiyah; Agus Yulianto; Mahardika Prasetya Aji (Physics Communication, 2025)
Textbook is one of the learning tools that commonly used by student. The purpose of this research is to describe the stages of developing a STEM based textbook integrated to Quranic verses and to measure of the effectiveness the textbook to enhance students conceptual understanding of traveling and standing wave and to acknowledge students insight to spiritual knowledge. This research used research and development method with 4D model. The 4D model consist of four stages developing process. Those are to define, design, develop and disseminate. The research subject were the students of XI MIPA3 of MAN Pemalang as for experimental class, and students of XI MIPA 4 of MAN Pemalang as a control class. Based on expert judgements this STEM based textbook was categorized to a valid and acceptable textbook for use in learning process with an average score 77.4%. The effectiveness of the STEM based textbook integrated to Quranic verses to enhance conceptual understanding was measured with the pretest-posttest control group design. The result showed that the textbook is effective in improving students conceptual understanding of traveling and standing wave subject.